Literature as Resistance: A Comparative Study of Double Marginalization of Women in Toni Morrison’s The Bluest Eye and Bibek Ojha’s Ailani - Roka, Prakash; Rai, Dipak Raj (NPRC Journal of Multidisciplinary Research, 2025)
Background: This study focuses on Pecola Breedlove, an African American girl, and Fulmaya Badi, a Dalit woman from Nepal’s Badi community, to explore how intersecting systems of racism, casteism, patriarchy, and poverty produce double marginalization. Toni Morrison’s The Bluest Eye and Bibek Ojha’s Ailani expose how racial and caste hierarchies, reinforced by gendered oppression and social exclusion, destroy women’s dignity, identity, and agency across distinct cultural contexts.Method: The paper employs a comparative literary analysis informed by intersectionality, Black feminist theory, postcolonial feminism, and Dalit feminist thought. Through these frameworks, it analyzes how internalized racism in Pecola and caste-based patriarchy in Fulmaya represent structural violence that silences and subjugates women.Findings: The study reveals that both novels depict oppression not as isolated experiences but as systemic and institutionalized practices that deny women autonomy and self-worth. Despite geographical and cultural differences, Pecola and Fulmaya experience similar mechanisms of dehumanization and exclusion embedded within their societies.Conclusion: Understanding the lives of doubly marginalized women requires an intersectional lens that connects race, caste, gender, and class as interlocking systems of domination. The study underscores the necessity of inclusive feminist literary criticism that amplifies subaltern voices and challenges hierarchies of power across cultures.Novelty: By bridging African American and Dalit feminist discourses, this research offers a transnational perspective on intersectional oppression, demonstrating how literature functions as a form of resistance that reclaims silenced narratives and envisions transformative justice.